Highlights on the properties of the soda-lime-silicate glass residue that enable its use as filler in ultra-high performance concrete (Research, Society and Development, 2021)
The exponential advancement of cutting-edge technologies in the scope of civil construction, seeks to give cement-based materials the eco-efficient potential linked to mechanical performance that enables different applications. This work aims to evaluate the glass residue regarding the pozzolanic potential through ABNT NBR 5752:2014, as well as to verify whether through the characterization tests of x-ray fluorescence, x-ray diffraction and laser diffraction granulometry, if it is viable of application as supplementary cementitious material (filler), in ultra-high performance concrete. The glass residue submitted to the tests proposed in this study, was crushed in a jaw crusher, milled in a bench ball mill at 47 rpm, and was sieved in a 75 µm opening mesh (ABNT nº 200 mesh). For the test of pozzolanic activity, CP II F-40 class cement, normal sand, water from the public supply network, and superplasticizer additive were used for the mix with 25% of the residue replacing cement, while for the other characterization techniques, the glass residue was applied in its processed form (after sieving), dry or wet. The evaluated glass residue did not reach the minimum rate of 75% established by ABNT NBR 5752:2014, achieving only 45.72%, being classified as non-pozzolanic, which indicates its inert behavior in the presence of calcium hydroxide. The characterization tests confirmed, based on the specialized literature on ultra-high performance concrete, its viability as a filler when adopted as an alternative raw material for presenting chemical and mineralogical composition, in addition to granulometric distribution, very close to those used in studies that demonstrated satisfactory results when using the glass residue as an input.